Actors, Orators, and the Boundaries of Drama in Elizabethan Universities. (20th November 2017) - Blank, Daniel
Abstract: This article discusses the debates over drama that took place in the English universities during the late sixteenth century. It reconsiders the career of the Oxford academic and theologian John Rainolds, whose objections to student performance are usually conflated with attacks upon professional drama. This article argues instead that his opposition arose largely from two related institutional concerns: the equation of drama with rhetorical exercises and the increasing use of spectacle in university plays. The controversy over theatrical performance is thus cast in a new light as an inquiry into the place and purpose of drama within university culture.